Simple Isolated Skull Fractures in Young Children: Findings From a Hospital‐Based Child Protection Team - Aisling Woods; Alice Johnson; Geraldine Goh; Erin Bock (Journal of Paediatrics and Child Health, 2026)
ABSTRACT Objective Isolated skull fractures (ISFs) in young children are a common reason for referral to hospital‐based child protection teams for forensic medical assessment. The purpose of this study was to describe the injury opinion of simple ISFs determined by a child protection team, and to assess the utility of skeletal survey and ophthalmology examination in forming the injury opinion. Methods A retrospective study was performed for children under 2 years referred to the child protection team at a tertiary children's hospital with a simple ISF between July 2015 and December 2024. The primary outcome was the injury opinion determined by the child protection team: accidental, indeterminate or inflicted. Secondary outcomes included the rate and positive yield of skeletal survey and ophthalmology examination. Results Of the 81 children referred with a simple ISF, 4 (5%) were considered inflicted, 30 (37%) indeterminate and 47 (58%) accidental. History with statutory child protection services ( p ‐value 0.042) and additional suspicious cutaneous injuries ( p ‐value < 0.001) were significantly associated with inflicted injury. A skeletal survey was obtained for 43 children (53%). Four skeletal surveys identified additional injuries, giving a positive yield of 9%. Ophthalmology examination was performed for 38 children (47%), and none had retinal haemorrhages. Conclusion ISFs in young children are rarely determined to be inflicted injuries. In cases of inflicted ISF, there are additional clinical factors prompting concern (age under 6 months, history with child protection services, or additional suspicious cutaneous injuries). Skeletal survey rarely adds additional information, and ophthalmology examination never adds additional information.